Intra-articular Placement of an Intraosseous Catheter. Issue 1 (8th December 2014) - Grabel, Zachary; DePasse, J. Mason; Lareau, Craig R.; Born, Christopher T.; Daniels, Alan H.
Abstract: Gaining vascular access is essential in the resuscitation of critically ill patients. Intraosseous (IO) placement is a fundamentally important alternative to intravenous (IV) access in conditions where IV access delays resuscitation or is not possible. This case report presents a previously unreported example of prehospital misplacement of an IO catheter into the intra-articular space of the knee joint. This report serves to inform civilian and military first responders, as well as emergency medicine physicians, of intra-articular IO line placement as a potential complication of IO vascular access. Infusion of large amounts of fluid into the joint space could damage the joint and be catastrophic to a patient who needs immediate IV fluids or medications. In addition, intra-articular IO placement could result in septic arthritis of the knee. Z Grabel, JM DePasse, CR Lareau, CT Born, AH Daniels .Intra-articular placement of an intraosseous catheter .Prehosp Disaster Med .2015 ;30 (1 ):1 -4 .